Cooling Effect of Crushed Rock-Based Embankment along the Chaidaer-Muli Railway - Ji Chen; Yu Sheng; Yaling Chou; Lei Liu; Bo Zhang (Advances in Materials Science and Engineering, 2015)
This paper presents an experimental study of the cooling effect of crushed rock-based embankment on slope wetlands along the Chaidaer-Muli Railway. The result shows that only the embankment shady side can be effectively cooled down in a warm permafrost region and the crushed rock-based embankment can cool the entire embankment in a cold permafrost region. The crushed rock-based embankment cannot eliminate the problems from the south-north slope. Slope wetland can influence the temperature field of the crushed rock-based embankment. On the uphill side, it will lead to degradation in some cases and development of permafrost in other cases, which depends on the topsoil water content and ground surface runoff. On the downhill side, it always leads to the warming of permafrost. For crushed rock-based embankment constructed on slope wetlands, it is necessary to adopt other stronger measures to eliminate the sunny-shady slope problems.